Spatio‐temporal analysis of Nova virus, a divergent hantavirus circulating in the European mole in Belgium. Issue 23 (9th November 2016) - Laenen, Lies; Dellicour, Simon; Vergote, Valentijn; Nauwelaers, Inne; De Coster, Sarah; Verbeeck, Ina; Vanmechelen, Bert; Lemey, Philippe; Maes, Piet
Abstract: Over the last decade, the recognized host range of hantaviruses has expanded considerably with the discovery of distinct hantaviruses in shrews, moles and bats. Unfortunately, in‐depth studies of these viruses have been limited. Here we describe a comprehensive analysis of the spatial distribution, genetic diversity and evolution of Nova virus, a hantavirus that has the European mole as its natural host. Our analysis demonstrated that Nova virus has a high prevalence and widespread distribution in Belgium. While Nova virus displayed relatively high nucleotide diversity in Belgium, amino acid changes were limited. The nucleocapsid protein was subjected to strong purifying selection, reflecting the strict evolutionary constraints placed upon Nova virus by its host. Spatio‐temporal analysis using Bayesian evolutionary inference techniques demonstrated that Nova virus had efficiently spread in the European mole population in Belgium, forming two distinct clades, representing east and west of Belgium. The influence of landscape barriers, in the form of the main waterways, on the dispersal velocity of Nova virus was assessed using an analytical framework for comparing Bayesian viral phylogenies with environmental landscape data. We demonstrated that waterways did not act as an environmental resistance factor slowing down Nova virus diffusion in the mole population. With this study, we provide information about the spatial diffusion of Nova virus and contribute sequence information that can be applied in further functional studies.